FAKTOR YANG MEMENGARUHI CASH HOLDING PADA PERUSAHAAN SEKTOR KONSUMEN NON PRIMER - Fedora, Jessica; Susanto, Liana (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research is to determine the effect of profitability, tangible asset, leverage, and firm size on cash holding of consumer cyclicals companies listed on Indonesia Stock Exchange for the period of 2019-2021. The sample in this research has been selected by purposive sampling method and the total sample is 76 companies. The data in this research has been processed by SPSS version 20 and Microsoft Excel 2016. The results of this research showed that tangible asset and leverage have a significant negative impact on cash holding, and profitability and firm size have no significant impact on cash holding. The implication of this research is expected to be able to provide the information about the factors that affect on cash holding in consumer cyclicals company, so the company’s management can carry out cash management by considering several factors such as profitability, tangible asset, leverage, and firm size. The results of this research are also expected to increase the awareness of importance of cash management to maintain the company liquidity. Company needs to maintain their liquidity by having an ideal cash holding level to avoid the financial distress or even bankruptcy.